1993
DOI: 10.1080/10605851.1993.10640924
|View full text |Cite
|
Sign up to set email alerts
|

Macrostructural Employment Shifts and Urbanization in the Former USSR: An International Perspective

Abstract: This paper examines the shifts in labor between the primary, secondary, and tertiary sectors (extractive industries, manufacturing and construction, and services and related activities, respectively) accompanying economic change in the former USSR and their relationship to patterns of urbanization. A major focus of the study is the comparison of the Soviet experience with trends seen in Western and Third World countries and the explanation of this regional variation. Emerging economic and political trends like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
1

Year Published

1993
1993
2004
2004

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
0
4
0
1
Order By: Relevance
“…At the same time, the low level of urbanity of many small Soviet industrial towns and semi-urban 'townlets' (poselki) provoked a discussion of over-or under-urbanisation (Ofer 1977;Gornostayeva 1989;Treyvish et al 1993). The terms and measures could be called into question, but the debaters agreed that the Soviet urban system was underdeveloped and urbanisation was incomplete (Pivovarov 1991, p. 9;Shaw 1999, p. 166).…”
Section: Soviet and Post-soviet Challenges To The Theory Of Urbanisationmentioning
confidence: 99%
See 2 more Smart Citations
“…At the same time, the low level of urbanity of many small Soviet industrial towns and semi-urban 'townlets' (poselki) provoked a discussion of over-or under-urbanisation (Ofer 1977;Gornostayeva 1989;Treyvish et al 1993). The terms and measures could be called into question, but the debaters agreed that the Soviet urban system was underdeveloped and urbanisation was incomplete (Pivovarov 1991, p. 9;Shaw 1999, p. 166).…”
Section: Soviet and Post-soviet Challenges To The Theory Of Urbanisationmentioning
confidence: 99%
“…After its third start, the U(II) stage lasted until the mid 1980s or early 1990s, despite lower growth rates. The late Soviet urban inertia resembles a hesitating tertiarisation of employment when the service sector grew slowly after it overtook the industrial sector during the 1970s (Treyvish et al 1993). Anyway, the new polarisation reversal looks more predictable and well timed.…”
Section: Stages Of Russian Urbanisation: Population Change and Net MImentioning
confidence: 99%
See 1 more Smart Citation
“…Market reforms in Moscow, embarked on the path of post-industrial development (Treivish, Pandit and Bond, 1993) without a clear roadmap, have revealed distinct characteristics of an "informational" city (Castells, 1989) as a stage on the way to "world city" status. Signs of such an evolution have included an office boom, visible in the rental prices and evident to all residents and visitors by the proliferation of cranes and construction sites in central Moscow (Vendina, 1997); the creation is increasingly clear that certain sites in the city are highly-prized while most of the city remains excluded from the new business developments.…”
mentioning
confidence: 99%
“…Transitionelle Ökonomien werden definiert über eine Kombination von Struktureigenschaften, die sowohl typisch sind für entwik-keltere als auch für weniger entwickelte Länder. In Anlehnung an TREIVISH et al223 werden vor allem international vergleichend die Verzerrung in der Drei-Sektoren-Struktur herausgestellt.Räume. Die Autoren halten hierbei folgende Struktureigenschaften für maßgebend: mit diesen Effekten verknüpfter Tatbestand sinkender Familiengrößen infolge steigender Pro-Kopf-Einkommen.…”
unclassified